STRATEGI PEMASARAN IKAN SALAI DI DESA KESUMA KECAMATAN PANGKALAN KURAS KABUPATEN PELALAWAN - Nia Oskarlina; Saipul Bahri (UIR Press, 2022)
Fresh fish from the catch that is processed into salai fish is a form of utilizing the potential of river natural resources in Kesuma Village. In its distribution, the salai fish business in Kesuma Village faces the problem of limited marketing reach. This study aims to analyze: (1) the current marketing mix strategy of the salmon business (2) Recommending the marketing strategy of the salai fish business in the future. This research was conducted for 6 months starting from November 2021 to April 2022. Sampling was carried out using the census method. The data analysis used consisted of the 7P, SWOT and QSPM approaches. The results showed that the condition of the salai fish business in Kesuma Village through the marketing mix produced a product with a distinctive taste and aroma, the price of the product was determined by the entrepreneur based on the type and number of fish caught, the business location was close to the river but far from crowds and markets, promotion still personal selling, always prioritizing polite and friendly service in the sales process, the process of getting the product can be through ordering or directly at the entrepreneur's house and the Sorek Satu Sunday market and the product has not been packaged. The results of the SWOT analysis show that the business is in quadrant I, namely the SO (Strength and Opportunities) strategy, namely increasing the quality and quantity of products offered, cooperation with restaurants and restaurants so that market share is wider, adding variants of product types and sizes. The priority strategy that has the highest level of attractiveness is the SO strategy, namely improving the quality and quantity of the products offered (STAS:5,39).